Dolutegravir-based maintenance monotherapy versus dual therapy with lamivudine: a planned 24 week analysis of the DOLAM randomized clinical trial. (28th March 2018) - Blanco, Jose L; Rojas, Jhon; Paredes, Roger; Negredo, Eugenia; Mallolas, Josep; Casadella, Maria; Clotet, Bonaventura; Gatell, Jose M; de Lazzari, Elisa; Martinez, Esteban; ,
Abstract: Background: No controlled comparisons between dolutegravir/lamivudine or dolutegravir maintenance therapy have been done. We hypothesized that these options would have similar efficacy to triple ART. Methods: We used an open-label non-inferiority randomized controlled trial comprising two phases: phase A was established to test that experimental arms did not have an unacceptable (≥5%) failure rate; phase B was intended to include the full number of patients followed for 48 weeks. Treated HIV-1-infected adults with viral load <50 copies/mL for ≥12 months, no prior viral failure or resistance mutations to study drugs, nadir CD4 >200 cells/mm 3, and hepatitis B virus surface antigen negative were randomized 1:1:1 to maintain triple therapy (control arm), or to switch to dolutegravir/lamivudine, or to dolutegravir monotherapy stratifying by anchor drug. Premature discontinuation was considered if viral failure or therapy interruption due to adverse events, concurrent illness, protocol deviation or patient's wish occurred. Blips were registered. Planned phase A results at 24 weeks are reported here. The study is registered at EudraCT: 201500027435. Results: Ninety-one (control, n = 31; dual therapy, n = 29; monotherapy, n = 31) patients were randomized. Three patients (none previously exposed to integrase inhibitors) prematurely discontinued treatment due to viral failure: dolutegravir/lamivudine ( n = 1), no resistance mutations (subject A); dolutegravir ( n = 2), N155H, S147G and Q148R resistance mutations (subject B), and E138K, G140S and N155H resistance mutations (subject C). There were no discontinuations for other reasons. One patient (dolutegravir/lamivudine) experienced a blip in viral load. The Data Safety Monitoring Board recommended stopping the dolutegravir monotherapy arm. Conclusions: In contrast to dolutegravir/lamivudine, a higher than expected risk of viral failure with development of cross-resistance integrase mutations occurred with dolutegravir maintenance monotherapy.